Analisis Pengaruh Konten YouTube “Rabbids Invansion” terhadap Pemerolehan Bahasa Anak Usia 3-5 Tahun di Era Digital - Erfriani Sekar Talenta Simangunsong; Arlin Septia Basana Siagian; Jesica Simanjorang; Fadilla Aura Ramadani; Ela Emayusnita Sirait; Rahma Hidayati; Kristin Dwi Amsari Pasaribu; Rosalina Tautainam; Johannes Bagas Sitorus; Rosmawaty Harahap; Hidayat Herman (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to examine the influence of the animated series Rabbids Invasion on language acquisition in children aged 3–5 years in the digital era. Rabbids Invasion, produced by Ubisoft Film & Television, TeamTO, and Nickelodeon Animation Studios, is popular among children both on television and YouTube. However, the series contains minimal meaningful dialogue, relying heavily on nonsensical sounds such as “Bwaaaaa,” which children tend to imitate. The research employed a qualitative descriptive method using direct observation of children’s language behavior and interviews with parents to gather in-depth information about their children’s responses to the program. The findings indicate that frequent exposure to this series is associated with limited vocabulary development and imitation of character gestures, expressions, and sounds, which can negatively affect daily communication skills. These results highlight the importance of parental guidance in selecting educational content that supports vocabulary growth, meaningful language input, and overall language development in early childhood.